2022
DOI: 10.3389/fmicb.2022.951782
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic-based characterization of the gut virome in patients with polycystic ovary syndrome

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is a complex disease that afflicts women of reproductive age, and its pathological mechanism has not been well explained. The gut microbiota is believed to be closely related to the development of PCOS. Although an important component of the gut microbiome, the role of the gut virome in the development of PCOS is still unclear.MethodsIn this study, we profiled and compared the gut viral community of 50 patients with PCOS and 43 healthy women based on the analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Viruses are considered to be important components of the gut microbiome, and recent studies have identified the interactions between viruses and bacteria that affect the biological health of the host through functional annotation [ 56 , 57 , 58 ]. Through our functional annotation and enrichment of the six vOTUs change patterns, we found that, among the constantly increasing vOTUs groups, there are some enriched functions related to viruses’ adaptability to the environment, such as salt response and heat response.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses are considered to be important components of the gut microbiome, and recent studies have identified the interactions between viruses and bacteria that affect the biological health of the host through functional annotation [ 56 , 57 , 58 ]. Through our functional annotation and enrichment of the six vOTUs change patterns, we found that, among the constantly increasing vOTUs groups, there are some enriched functions related to viruses’ adaptability to the environment, such as salt response and heat response.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that even alpha diversity indexes describing the characteristics of the microbiota of each individual patient provide information that makes it possible to distinguish the microbiome of a healthy person from a patient with a “classic” PCOS phenotype. Notably, in addition to the gut microbiome, other biotopes of patients with PCOS are being actively studied, for example, the oral cavity [ 48 , 49 ], vaginal microbiome [ 50 , 51 , 52 ], blood bacteria spectrum [ 53 ], and gut virome [ 54 ]. Undoubtedly, for a comprehensive characterization of the microbiome in PCOS, it is necessary to consider a complex of factors of bacterial origin.…”
Section: Discussionmentioning
confidence: 99%
“…A gut virus catalog comprising over 67,000 nonredundant viral operational taxonomic units (vOTUs) was constructed from over 10,000 publicly available fecal metagenomes from the Chinese population ( 28 ). Protein-coding genes of the vOTUs were predicted using Prodigal ( 29 ) with the option “-p meta.” Taxonomic classification of vOTUs was performed based on protein sequence alignment to the combined database derived from the National Center for Biotechnology Information RefSeq database, the Virus‒Host database ( 30 ), the crAss-like protein sequences from Guerin’s study ( 31 ), and the viral protein sequences from Benler’s study ( 32 ).…”
Section: Methodsmentioning
confidence: 99%